can someone help me pls?
1 answer:
Answer:
<h2>
decreasing: (-2, -1)∪(-1, 0) </h2>
Step-by-step explanation:
From x = -2 to x = 0 function is decreasing, but for x= -1 function doesn't exist, so we need to exclude x = -1 from (-2, 0)
You might be interested in
Answer:
100% its 2 my guy trust meeee
Answer:
6 and 8
Step-by-step explanation:
6+8=14 difference 2
Hello :
f(x) = (x-5)(x+2i)
= x² +2ix -5x-10i
f(x) = x² +(2i-5)x -10i
<span>coefficients : a =1 b = 2i-5 c =-10i</span>
X=_________
or
y=_________
Most likely it will be x=s.
Your answer is <span>–4.9t^2 + 15t + 1 = 0
Hope this helps.
</span>